The socio-economic rank of parents and students’ academic and cognitive outcomes: Examining the physical, psychological and social mediators - Nja, Cecilia O.; Neji, Hope A.; Orim, Richard E.; Ukwetang, John O.; Ideba, Mary A.; Cornelius-Ukpepi, Bernedette; Ndifon, Rita A. (Frontiers in Education, 2022)
A cross-sectional observational type of survey design was used in this study to provide an all-encompassing evaluation of how family income is correlated with multiple cognitive and academic outcomes of senior secondary science students. It was aimed at examining the bedrock of physical and psychosocial mechanisms that influences students' learning and cognitive attitude using a self-reporting questionnaire labelled Socio-Economic Rank and Students Outcome Questionnaire (SERSOQ) A sample size of 584 senior secondary science students was used for this research. Analysis of data collected was done using regression analysis, percentage, and mean. There was a great correlation between family income and academic achievement, cognitive attitude, and study habits. The study did not find a significant relationship between assignments with the variables under investigation. Importantly, the findings of this study found that parental control exhibited the greatest mediating function in providing family income impact on students' cognitive attitude. Other mediators like students' and peers' educational ambitions as well as mother-child verbal relationships were discovered as potent mechanisms. Findings also showed a slight impact of family income on parent-child and mother-father relationships. Parental control consists of an influential setting that is outside the school environment yet mounting a very powerful effect in determining school outcomes in adolescents. This paper contributes to a better knowledge of how family economic recourse is distributed to academic achievement, cognitive attitude, and study habits of their children as presented through students' agency as well as peer influence. Recommendations for further research have been made.